The correlation between economic indicators and taiwan stock market - a case study of leading and lagging indicators - Lori Tzu-Yi Yang (Financial Studies, 2020)
This study investigates the correlation between economic indicators and Taiwan stock market, analysing the leading and lagging indicators from January 1995 to December 2016 to determine whether there is any significant correlation between the indicators and the stock market. With Large-cap Stock Price Index as dependent variable and the leading and lagging indicators as independent variables, and the correlation between the leading and lagging indicators and Taiwan Stock Exchange Corporation (TSEC) Large-cap are empirically analysed by multiple regression analysis in Eviews 9. It is concluded that there is both a significant and positive correlation between the leading indicator of the Index of Export Orders and the closing price of TSEC Large-cap Stocks anda significant and negative correlation between the lagging indicators of Unemployment Rate and Inventories to Sales Ratio for Manufacturing and TSEC stock price.
Keywords: D53; E44; G10; 330; TSEC Large-cap Index; leading indicators; lagging indicators